Comparison of Diazepam and Phenytoin in Patients of Less Than One Year with Status Epilepticus - Zaman, Muhammad Saqib; Siraj, Karishma; Ahmad, Mansoor; Waqar, Muhammad; Hameed, Abdul (Indus Journal of Bioscience Research, 2025)
Background: Status epilepticus in children is a critical emergency and requires prompt treatment to avoid long term consequences. Anticonvulsants such as phenytoin and diazepam are used commonly to treat this condition. But while the two drugs are very different, there’s still no consensus on which is more effective in young children. Objective: To compare the efficacy of diazepam and phenytoin in children less than one year of age with status epilepticus. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from February 2024 to August 2024 at the Department of Pediatric Medicine, LRH Peshawar. Methodology: Sixty children, 1–12 months old with status epilepticus were randomly assigned into two groups; Group A (phenytoin), n = 30 and Group B (diazepam), n = 30. Diazepam was given at 0.2 mg/kg, and phenytoin at 15–20 mg/kg. Cessation of seizures within 10 minutes and no recurrence within 12 hours was measured as efficacy. And they analyzed data using IBM SPSS version 26 and set statistical significance at p. value. Results: Group B (diazepam) showed a significantly higher seizure cessation rate (83.3%) compared to Group A (46.7%) (p=0.006). Stratified analyses indicated that diazepam was particularly more effective in female patients (p=0.011) and those with a lower body weight (≤8 kg) (p=0.015). Additionally, for complaints lasting longer than 24 hours, diazepam had a markedly higher efficacy (88.9% vs. 5.9%, p=0.000). Conclusion: Diazepam is more effective than phenytoin for managing status epilepticus in children under one year of age. The results support the use of diazepam as the first-line treatment due to its rapid onset of action and superior efficacy, particularly in patients with lower body weight and longer duration of seizures.